Aktivitas Antibakteri Fraksinasi Ekstrak Daun Pandan Wangi (Pandanus amaryllifolius) Terhadap Bakteri Escherichia coli Menggunakan Metode KLT-Bioautografi - Latif, Safira Kartika Handayani; Naid, Tadjuddin; Fitriana, Fitriana (PHARMACY UMI JOURNAL SYSTEM, 2023)
Fragrant pandan leaves (Pandanus amaryllifolius) have antibacterial abilities, which have secondary metabolites of alkaloids, flavonoids, tannins and saponins. The purpose of this study was to determine the antibacterial activity of extract fractionation from pandan leaves (Pandanus amaryllifolius) against Escherichia coli bacteria. This study used fragrant pandan leaf simplicia (Pandanus amaryllifolius) and extracted using the maceration method with 96% ethanol solvent and evaporated with a rotavapor, after which it was fractionated with ethyl acetate solvent and evaporated again using a rotavapor. The ethyl acetate fraction of fragrant pandan leaves (Pandanus amaryllifolius) was subjected to a screening test with a concentration of 2% against Escherichia coli bacteria, and a TLC-Bioautography test was carried out followed by identification of the chemical components. The result of the 2% concentration screening test on the ethyl acetate fraction of fragrant pandan leaves (Pandanus amaryllifolius) showed activity against Escherichia coli bacteria. TLC-Bioautography test result showed activity on Escherichia coli bacteria with Rf values of 0,94 and 0,65. The result of chemical identification of the ethyl acetate fraction of fragrant pandan leaves (Pandanus amaryllifolius) were positive for containing chemical compounds of flavonoids and tannins which can be used as antibacterials.